Respon Pertumbuhan Jagung Lokal Pulut dan Siropu Gorontalo Terhadap Cekaman Kekeringan - Jusna Ahmad; Patta Sija; Kadita P. Latif; Novri Y. Kandowangko (Jurnal Biologi Papua, 2023)
In Indonesia, maize has a number of growth constraints and one of which is climate factor. The objective of this research was to determine the growth response of local maize variety. This research was conducted by applying a factorial Randomized Block Design (RBD) with two factors. The first factor is variety (V): pulut, siropu and jakaring (comparison) while the second factor is drought treatment (K) which comprises three treatments including control, drought for 45-55 days after planting (DAP), and drought for 55-65 DAP. In this case, all treatments are repeated three times. The research revealed that the growth of maize indicate different responses towards variety as shown by parameters of plant height, soil moisture content, cob diameter, cob length, cob weight with husks, cob weight without husks, dry weight of root, and number of cob row. Meanwhile the drought stress does not indicate significant response towards growth of maize the drought-tolerant variety of maize with parameter of number of cob raw is siropu local maize.Key words: staple food; local corn; drought stress; growth.